Extração sem solvente de compostos bioativos de mirtilo assistida por ultrassom - Lucas, Bruna Nichelle (2018)
Conventional techniques for extracting bioactive fruit compounds employ long periods of extraction and high consumption of toxic solvents. However, there is growing interest in extracting safer, less toxic and environmentally friendly extracts. Ultrasonic assisted extraction is an innovative technique in the field of green chemistry, which seeks to obtain active extracts and offers no risks to nature and the operator, being a simple, fast and reproducible extraction technique. Thus, the present work aims to evaluate the effect of ultrasonic assisted extraction without using any solvent to obtain total phenolic compounds of blueberry. For that, the process was optimized through the surface response methodology, evaluating time, sample weight and amplitude, in order to obtain the best extraction conditions. Based on the response methodology, the best conditions found were 15 g of sample for a time of extraction of 7 min and with amplitude of the equipment of 50%, resulting in a total phenolic value of 197.58 ± 0.63 mg of GAE.100g-1. In addition, the proposed method was compared with the microwave extraction method (MHG), conventional (without solvent use) and ultrasonic assisted extraction with refrigerated bath, in the parameters of total phenolic content, monomeric anthocyanins antioxidant capacity and phenolic composition. Ultrasound-assisted extraction without solvent showed higher yields (generally about 63%) compared to other solvent-free methods, showing an innovative, efficient and environmentally friendly extraction method.